La contribution d’Antonio Buero Vallejo au théâtre de science-fiction espagnol - Miguel Carrera Garrido (ReS Futurae, 2021)
Science fiction in the theatre is not a subject that has received much attention from the scientific community. There are still many scholars – in science fiction and theatre – who believe that this genre is difficult to put on the stage satisfactorily. At the same time, however, numerous works have shown the existence of a whole body of pieces in this field, little explored and yet to be definitively categorized. These studies are complemented by others of theoretical nature, which demonstrate the viability of science fiction theatre. Building on both types of work, this article wants to claim the contribution to the genre of one of the most important Spanish playwrights of the twentieth century: Antonio Buero Vallejo. Even if the affinity of part of his production with science fiction has already been underlined by certain critics, this connection remains to be studied in depth. By focusing on one of Buero’s most iconic pieces - La Fundación (1974) - this is what this article aims to do.